Decomposing the urban-rural welfare gap in Sri Lanka - Nirodha Bandara; Simon Appleton; Trudy Owens (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2018)
This paper explores the urban-rural welfare gap in 2002 and 2009/10 for the case of Sri Lanka. This was a period of high growth and falling poverty rates in the country. The paper attempts to explore three issues: (a) what are the determinants of urban and rural household welfare, (b) does the urban-rural welfare gap rise or fall between 2002 and 2009/10, and (c) what factors contribute towards the widening or narrowing of the urban-rural welfare gap over time. The paper contributes to existing literature using a new method of unconditional quantile regression to examine the determinants of per capita expenditure for urban and rural households across the expenditure distribution. Further, this method enables us to isolate and identify the characteristics that contribute towards the urban-rural divide in welfare. For this, a variant of the threefold Blinder-Oaxaca decomposition is applied directly to the estimation results of the unconditional quantile regression. We find the urban-rural welfare gap to have fallen considerably between 2002 and 2009/10. At a given point in time, the welfare gap is larger between richer urban and rural households relative to poorer households.
Keywords: C31; O12; R11; 330; unconditional quantile regression; urban-rural welfare gap; Blinder-Oaxaca decomposition; Sri Lanka